Influencia de la actividad productiva de la colección de cacao en la calidad del suelo de la ESPAM MFL - Cedeño López, Luis Ivan (2017)
The objective of this research was to evaluate the influence of Productive Activities Collection cocoa ESPAM MFL on Environmental Quality soil. He ran as nonexperimental research using descriptive method and interview techniques. Working time was nine months during the period August 2014 - May 2015. The results showed that cocoa collection is characterized by various activities and sequences thereof were identified as: planting land clearing, clones, and plant maintenance pruning, fertilizing, and harvesting kills spiteful. Physical-Chemical Analysis of paragraph soil were performed measuring environmental quality of it, in the laboratory of soil and plant tissue waters "Pichilingue" Tropical Experimental Station, here for which two samples was taken from 11 subsamples same Were homogenized Get To An aliquot. Getting the values of ammonium and low organic matter found the child with a regarding of phosphorus and potassium are in the Higher Level; Also establishing which textual soil class is between Franco and clay loam. With the results of the activities and analyzes proceeded to make a technical guide of cocoa handled with ecological techniques, para Improving Quality of Production Process cocoa cultivation in Relation to Soil Environmental Quality.